Evolution of philosophical views of I. Franko is on the Ukrainian idea in the context of contemporary problems - Sabadukha, Volodymyr (Skhid, 2013)
The author studies the I. Franko’s views upon the national ideal of the Ukrainian state development and the role of intelligentsia in national idea realization.